Rehabilitation with removable dentures in adults and older people with partial or total edentulism: Chilean Public Health System Experience, 2017–2019 - Karen Danke, DDS, MSc; Ingeborg Bevensee, DDS; Ana Beatriz Silva, DDS, MSc; Alicia Morales, DDS, MSc; Gisela Jara, DDs, MSc; Fabiola Werlinger, MSc, PhD; Mauricio Baeza, DDS, MSc, PhD; María Ignacia Muñoz, DDS; Viviana García Ubillo, MSc; Jorge Gamonal, DDS, MSc, PhD (Archives of Gerontology and Geriatrics Plus)
Statement of problem: Tooth loss is frequent among the Chilean population, particularly the poor and elderly. The Public's response is mostly via removable dentures (RDs), however there is limited evidence regarding its results. Purpose: The objective of this descriptive ecological study is to monitor and characterize the production of RDs within Chile's Public Health System. Material and methods: Public records were obtained from the Department of Statistics and Health Information of Chile (DEIS) website. All records regarding RDs activities within the Public Health System for years 2017 to 2019 were retrieved and included in the analysis. Results: Between 2017 and 2019, the Public Health sector delivered an average of 342,261 RDs annually, which corresponds to 2.4 RD per 100 individuals. Overall, 70.3 % of beneficiaries were female, 63.2 % were for people between the ages of 20 to 64, and 35.3 % were for people aged 65 or older. Among RDs provided, 57 % were made at the primary level and 43 % at the secondary level of care. The program “More Smiles”, accounted for 52.3 % of primary healthcare RD delivery. At the secondary level, 14.9 % of RDs had metallic framework, while 85.1 % were acrylic. Older persons and males were more likely to receive acrylic RDs than their counterparts. Conclusions: RDs are regularly supplied in Chile's Public Healthcare System, mainly through primary care. The characterization regarding programs, type of RDs, gender and age of the recipients, may guide future hypothesis regarding the adequateness of the response to address tooth loss at a population level. Further investigation into the impact on patient satisfaction and RD quality is recommended to enhance understanding in this domain. Clinical implications: The study explores the scale and characteristics of removable prosthetic provision within Chile's Public Health System. This comprehensive overview enables the identification of areas requiring further attention to ensure the delivery of high-quality treatments and the efficient allocation of public resources.